Postoperative complications and myocardial injury in patients receiving air or oxygen. Prospective, randomised and pilot study. Issue 10 (29th August 2022) - Valadkhani, Arman; Henningsson, Ragnar; Nordström, Johan L.; Granström, Anna; Hallqvist, Linn; Wahlgren, Carl Magnus; Peterzén, Bengt; Eriksson, Julia; Bell, Max; Gupta, Anil
Abstract: Background: Supplementary oxygen is administered during anaesthesia to increase oxygen delivery and prevent hypoxia. Recent studies have questioned this routine. In this pilot study, our main aim was to investigate if 21% oxygen compared to ≥50% reduces the risk of postoperative complications and myocardial injury. Methods: In this pragmatic, multicentre, single‐blind study, patients undergoing vascular surgery were randomised to receive a fraction of inspired oxygen (Fi O2 ) ≥ 0.50 and oxygen saturation determined by pulse oximetry (SpO2 ) ≥ 98% (group H) or Fi O2 of 0.21 and SpO2  > 90% (group N) oxygen perioperatively. The primary outcome was a composite outcome of major pre‐defined postoperative complications assessed at 30 days. Myocardial injury was determined by serial troponin measurements. Data were analysed using generalised estimating equation, Mann–Whitney U test or chi‐squared test, as appropriate. Results: The 191 patients were randomised, and per‐protocol principle was used for analyses. At 30‐day follow‐up, 43 out of 94 patients (46%) had a postoperative complication in group H and 36 out of 90 patients (40%) in group N, p  = .46. New myocardial injury was seen in 27% versus 22% in Groups H and N respectively ( p  = .41). No differences in other outcomes were observed between the groups. Twelve patients (13%) in Group N had SpO2  < 90%, six recovered spontaneously and six required supplemental oxygen. At 1‐year follow‐up, one patient in group H had died. Conclusion: In this pilot study, postoperative complications were similar between the groups in patients randomised to Fi O2 of 0.21 or ≥0.50 and no difference was found in the incidence of new myocardial injury. Larger, prospective adequately powered studies are needed.